Congenital heart defects and skeletal malformation syndrome with congenital hemiplegia - Teli, Balakrishna; Biradar, Sneha (International Journal of Advances in Medicine, 2021)
Congenital heart defects and skeletal malformation syndrome is very rare syndrome. Most of the patients had germline mutations in ABL1 gene. A 30-year-old gentleman presented with history of congenital heart disease (ventricular septal defect) and skeletal malformations which are typical of CHDSKM. Patient also had congenital hemiplegia which is rare in CHDSKMS. Patient also had lactose intolerance since childhood. Patients were evaluated thoroughly to rule out other causes. Current report is one of the rare case reports of CHDSKMS, only few case reports have been published till now.